Membangun Strategi Mobilisasi Sumber Daya Adaptasi Dan Mitigasi Perubahan Iklim Di Desa Jolotigo Kecamatan Talun Kabupaten Pekalongan - Afandi, Muslim; Sumino, Sumino; Daryanto, Daryanto; Fahruzzaman, Fahruzzaman; Dinoyo, Ronggo (Community Development: Jurnal Pengembangan Masyarakat Islam, 2025)
Developing a Resource Mobilization Strategy for Climate Change Adaptation and Mitigation in Jolotigo Village, Talun District, Pekalongan Regency. This research focuses on community vulnerability as a result of climate change, types of threats, impacts, efforts that have been made, impact assessment, and types of mitigation adaptation actions. The aim is to analyze mitigation adaptation actions to control climate change. The fundamental problem that occurs as a result of climate change is a high level of vulnerability due to threats to people's livelihood sources, while community capacity is still low. This research uses the PAR (participatory action research) method with a participatory approach. Involving various elements of society in analyzing problems, planning actions, and of course trying to integrate with related policies. Data collection uses PRA (participatory rural appraisal) techniques such as seasonal calendars, socio-spatial mapping, trends and change. The results of this research show that there are various potential mitigation adaptations in controlling climate change in society. Various resources that can be managed are alternatives in increasing mitigation adaptation actions both internally and externally